Response of malt barley (Hordeum vulgare L.) varieties to nitrogen and sulphur application under Agro-climatic zone IIIa (semi-arid eastern plain zone) of Rajasthan - Parashar, Aabha; Kumar, Sudesh; Gupta, Shweta; Dogra, Prerna; Tyagi, B S (Journal of Cereal Research, 2025)
Field studies were carried out to investigate the effect of different nitrogen and sulphur applications on growth parameters, yield and quality parameters of two row malt barley varieties conducted at research farm, Rajasthan Agricultural Research Institute, Durgapura for two consecutive rabi seasons 2015-16 and 2016-17 on loamy sand soil. The twenty seven treatment combinations consisting of 3 varieties (RD 2849, DWRUB 52 and RD 2668), 3 nitrogen levels (60 kg, 90 kg and 120 kg) and 3 sulphur levels (0 kg, 10 kg and 20 kg) were tested in factorial randomized block design with three replications. The results indicated that variety RD 2849 proved significantly superior to DWRUB 52 and RD 2668 with respect to yield (grain and straw yield (q ha-1)) and quality parameters (Bold and Thin grain (%), Hectoliter weight (kg hl-1). In case of nitrogen and sulphur applications, chlorophyll content (%) at flag leaf stage and flag leaf area (cm), grain and straw yield (q ha-1), Nitrogen and Sulphur content (%) in grain and straw and bold and thin grain (%) and hectoliter weight (kg hl- 1) of barley were improved. The highest chlorophyll content (%) at flag leaf stage and flag leaf area (cm), grain and straw yield (kg hl-1), Nitrogen and Sulphur content (%) in grain and straw and bold, thin grain (%) and hectoliter weight (kg hl-1) of barley obtained with 120 kg N ha-1 and 20 kg S ha-1 and it was found statically at par with 90 kg N ha-1 and 10 kg S ha-1 application. DOI.10.25174/2582-2675/2020/85266